2017
DOI: 10.3390/genes8010031
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Transcriptome and Gene Expression of Brain Tissue in Sevenband Grouper (Hyporthodus septemfasciatus) in Response to NNV Infection

Abstract: Grouper is one of the favorite sea food resources in Southeast Asia. However, the outbreaks of the viral nervous necrosis (VNN) disease due to nervous necrosis virus (NNV) infection have caused mass mortality of grouper larvae. Many aqua-farms have suffered substantial financial loss due to the occurrence of VNN. To better understand the infection mechanism of NNV, we performed the transcriptome analysis of sevenband grouper brain tissue, the main target of NNV infection. After artificial NNV challenge, transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 57 publications
(61 reference statements)
1
11
1
Order By: Relevance
“…Thus, a significant up-regulation of antiviral proteins and NK-Lysin, a known antibacterial protein, was observed in the brain of NNV infected sevenband grouper (E. septemfaciatus). Furthermore, several chemokines, cathepsins and lepsins were also up-regulated [239]. Brain tissue was also analyzed in persistently infected Malabar grouper (E. malabaricus), showing that highly immune cell active signaling and surface receptor expression were triggered during persistent infection, as well as the interferon-induced response [236].…”
Section: Host Responsementioning
confidence: 99%
“…Thus, a significant up-regulation of antiviral proteins and NK-Lysin, a known antibacterial protein, was observed in the brain of NNV infected sevenband grouper (E. septemfaciatus). Furthermore, several chemokines, cathepsins and lepsins were also up-regulated [239]. Brain tissue was also analyzed in persistently infected Malabar grouper (E. malabaricus), showing that highly immune cell active signaling and surface receptor expression were triggered during persistent infection, as well as the interferon-induced response [236].…”
Section: Host Responsementioning
confidence: 99%
“…Such investigations have been performed in grouper kidney cells (GK cell line) [5], Asian sea bass epithelial cells (SB cell line) [6], European sea bass leukocytes [7], striped snakehead fish cells (SSN-1 cell line) [8] and European sea bass brain cells (DLB-1 cell line) [9]. The in vivo effect of NNV has also been analysed by RNA-Seq in the brain of sevenband grouper [10], pooled brain/eye and head kidney samples from Senegalese sole [11], the brain of Malabar grouper [12], and the liver, spleen and kidney of Epinephelus moara [13]. However, the in vivo response of European sea bass remains almost completely unexplored, and only a small number of publications have reported the modulation or involvement of immune factors in different tissues of D. labrax infected with NNV [14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The number of down-regulated genes was higher than up-regulated genes, suggesting that virus infection affects the expression of genes and lead to dysfunction. In another study, 628 DEGs were identified in the adult sevenband grouper after NNV infection (Kim et al 2017). The DEGs in this study will help identify causative genes for NNV resistance.…”
Section: Degs Of Brain Rna-seq Located In the 17 Mbp Region Involved In Immunity And Neuron Developmentmentioning
confidence: 79%
“…In this study, the number of reads was greater than the RNA-seq reads from other studies. For examples, about 45.1 million reads per library is obtained in sevenband grouper (Hyporthodus septemfasciatus) brain RNA-seq for NNV infection (Kim et al 2017). Therefore, the number of reads was sufficient for subsequent analysis to identify DEGs in brain RNA-seq.…”
Section: Data Acquisition Of Asian Seabass Brain Rna-seq After Nnv Challengementioning
confidence: 99%